Characteristics of Peanut Oil and Peanut Meal Produced by Extraction Using an Oil Press Machine - Ruri Wijayanti; Malse Anggia; Meiki Eru Putra; Robert Pratama Putra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Mechanical extraction of peanut oil using an oil press machine is a relatively simple and environmentally friendly method that can be applied on a small- to medium-scale. This study aimed to determine the characteristics of peanut oil and meal produced by an oil press. The research method employed was experimental and involved a descriptive analysis of the quality parameters of the oil and meal. For the oil, the observed parameters included yield, color  (CIELab), and density. For the peanut meal, the observed parameters were moisture, fat, and protein content. Results showed that increasing the extraction temperature increased the yield and density of peanut oil, with the highest values obtained at 200 °C. The lightest oil color was obtained at 180 °C, as indicated by the highest L* value. For the peanut meal, increasing extraction temperature decreased moisture content, with the lowest at 200 °C. However, the meal's residual fat content increased significantly at 200 °C, indicating decreased extraction efficiency at excessively high temperatures. The protein content of the meal ranged from 45.84% to 48.73% and remained relatively stable across all temperature treatments. These results indicate that the characteristics of the resulting peanut oil and meal are affected by extraction temperature; therefore, the extraction temperature must be selected according to the intended use of the final product. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land